The threat of political extraction and corporate cash holdings: The case of the GCC countries - Ghada Tayem (Cogent Economics & Finance, 2023)
This study examines the motives of corporations in the Gulf Cooperation Council (GCC) countries to hold cash with a focus on institutional characteristics related to the threat of political extraction. Using firm-level financial data and macro-level and institutional data and applying the GMM estimation method, the study finds that corruption (a proxy of the threat of political extraction) is positively related to cash holdings which suggests that the risk of political extraction induces GCC firms to accumulate cash to make political payoffs and preserve their financial flexibility. In terms of firm-level characteristics, GCC firms follow a pecking order as they deplete more cash the larger their capital expenditures. In addition, GCC firms save cash for transaction and precautionary purposes as indicated by the negative relation between cash and cash substitutes. This is the first study to examine the threat of political extraction on cash holdings using the context of the GCC, a cash-rich region with unique institutional settings. The findings on the GCC countries contribute to the ongoing debate regarding the political extraction-cash holdings relationship by examining a context under which corruption is likely to exert a positive impact on the level of cash holdings.
Keywords: G30; G32; 330; cash holdings; corruption; GCC; political extraction